Does Virtual Brain Autopsy Could be Used as a Clue for Detection of Personal Identity? (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: virtual autopsy nowdays show great success in human identification. Nowdays singleComputerized tomography of the brain could help answering many questions regarding the identity ofhumans, it could lead us to the gender ,weight and height roughly of the person in question.Patients and Methods: cross- sectional study during the period April 2019 till Mars2020 , One hundredand fifty participant aged between 15 and 29 years old were envolved in the current study after taking theirwritten and verbal consent or their caregiver and doing C T Brain for every one of the studied participant.Results: brain volume is statistically significant with weight , height, gender of the studied participant hencewe could use CT Brain to know the brain volume and then we could suspect weight , height and even genderso we can reach to the identity of the individual.Conclusion: We me be no longer in need of doing autopsy where virtual autopsy could find the answer tomany questions in research, where a correlation was found between brain volume ,gender, weight and height.
Keywords: computerized tomography Gender, height, virtual, weight.